Let's solve each equation to find the right match.
![2(e^(3t))=12](https://img.qammunity.org/2023/formulas/mathematics/college/ij2297sexn5bmwu7zmpsygpa2r78ke9d13.png)
First, we divide the equation by 2.
![\begin{gathered} (2(e^(3t)))/(2)=(12)/(2) \\ e^(3t)=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w5ywitwll1pvh01vxzmeh59uyhxisvn3yp.png)
Then, we apply logarithms on each side.
![\begin{gathered} \log _e(e^(3t))=\log _e(6) \\ 3t=\log _e(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/faa7w7xusadptoj8v5gyy2r19n3sf8x9f8.png)
So the first expression matches the first answer choice.
The second equation is
![12(e^(3t))=2](https://img.qammunity.org/2023/formulas/mathematics/college/npi8lvpan3jemhhgb2pl403q8e4ypva1y5.png)
First, we divide the equation by 12.
![\begin{gathered} (12(e^(3t)))/(12)=(2)/(12) \\ e^(3t)=(1)/(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ktode4su16cntvn1625u3rnw3n9ksogl9h.png)
Then, we apply logarithms on each side.
![undefined]()